PENGARUH PRODUCT USABILITY DAN CASHBACK PROMOTION TERHADAP KEPUASAN SERTA DAMPAKNYA PADA LOYALITAS PENGGUNA DOMPET DIGITAL “SHOPEEPAY” DI KOTA PEKANBARU - Salahudin Salahudin; Restuti Sri; Jusherm Jusherm (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study intends to ascertain the influence of cashback promotions and productusability on customer satisfaction and brand loyalty among "shopeepay" digitalwallet users in Pekanbaru City. All residents of Pekanbaru City who utilize theShopeePay digital wallet make up the study's population. A questionnaire was usedto gather primary data, which was used to support the study's findings. Pathanalysis with the aid of the program SPSSsampling technique is ProbabilitySampling, which offers equal opportunities for members of the population to bepicked as samples in this study. With a total of 110 respondents, the Hair et. al.sample size was used in this investigation. The findings of this study suggest that:1) Customers' satisfaction with products in Pekanbaru City who use ShopeePaydigital wallets is positively and significantly impacted by product usability. 2) InPekanbaru City, Cashback Promotion has a favorable and considerable impact onShopeePay digital wallet user happiness. 3) In Pekanbaru City, customersatisfaction has a favorable and considerable impact on users' loyalty. 4) InPekanbaru City, ShopeePay digital wallet customers' loyalty is positively andsignificantly impacted by product usability. 5) In Pekanbaru City, CashbackPromotion has a favorable and considerable impact on ShopeePay consumers'loyalty. 6) Product usability has a big impact on Pekanbaru City ShopeePay users'loyalty through satisfaction. 7) In Pekanbaru City, Cashback Promotionsignificantly affects ShopeePay digital wallet customers' Loyalty throughSatisfaction. Keywords: Product Usability, Cashback Promotion. Satisfaction, Loyalty,ShopeePay